2012
DOI: 10.1111/j.1474-8673.2012.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and functional studies for M3 muscarinic receptors and cyclo‐oxygenase‐2 expressed in the mouse atrium

Abstract: In mouse atrium, M₂ and M₃ muscarinic receptors (M₂R and M₃R) are involved in biphasic (negative and positive) inotropic actions of muscarinic agonists, and the positive inotropic action is reduced by indomethacin. The aim of our study was to determine the localization of M₂R, M₃R and cyclo-oxygenase (COX) in mouse atrium and to characterize muscarinic receptor-mediated positive inotropy. M₂R immunoreactivity was found only on atrial myocardium, but M₃R immunoreactivity was localized on both the myocardium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the studies using atria and ventricles, several studies demonstrated that M 3 receptor stimulation increased prostaglandin (PG) production in the endocardial endothelium which caused positive inotropy in the mouse atria [1417]. In contrast, Ateş and Kaygisiz reported that the positive inotropy was not dependent on PG production in rat hearts [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies using atria and ventricles, several studies demonstrated that M 3 receptor stimulation increased prostaglandin (PG) production in the endocardial endothelium which caused positive inotropy in the mouse atria [1417]. In contrast, Ateş and Kaygisiz reported that the positive inotropy was not dependent on PG production in rat hearts [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been thought that coronary artery spasm was related to the decrease of M 3 -mAChR ′s density [32] and it has demonstrated both an endothelium-dependent relaxation to acetylcholine in coronary circulation mediated predominantly by the activation of M3-mAChR [33] and a M 3 -mAChR mediated vasoconstriction in vascular smooth muscle cells in the absence of endothelium [19]. It has also demonstrated an endocardial endothelial M Rs mediate positive inotropy in response to muscarinic agonists via activation of COX-2 [34]. Further study is needed to evaluate differences in M 3 -mAChR signaling caused by changes in receptor desensitization, sequestration [35][36][37][38][39], and up-or down-regulation and to elucidate the role of M 3 -mAChR in cardiovascular system as well in inflammation and in cancer while new findings are emerging as regards the use of cardiovascular drugs [38,55,68,69,74,75,[77][78][79]82].…”
mentioning
confidence: 99%
“…In experimental conditions, acetylcholine (ACh) and carbachol (CCh) produces positive inotropic effects in isolated rat hearts (Ates et Kaygisiz, 1998) and biphasic inotropic response transient decrease in contractility followed by an increasein isolated mice left atria (Tanaka et al, 2001;Hara et al, 2009). The increase in contractile force is mediated by type 3 muscarinic acetylcholine receptors via activation of COX-2 enzyme (Harada et al, 2012).…”
Section: Other Possible Mechanism Of Cardiac Actions Of Ibuprofenmentioning
confidence: 99%